Limitations of standard cost-effectiveness methods for health technology assessment of treatments for rare, chronic diseases: a case study of treatment for cystic fibrosis. (31st December 2022) - Rubin, Jaime L.; Lopez, Andrea; Booth, Jason; Gunther, Penilla; Jena, Anupam B.
Abstract: Objectives: Cost-effectiveness analysis (CEA) is useful to assess the value of health care interventions based on clinical effectiveness and costs. However, standard CEA methods make important assumptions that may significantly increase the incremental cost-effectiveness ratio (ICER) for lifelong treatments for rare, chronic diseases. We used the cost-effectiveness of elexacaftor/tezacaftor/ivacaftor and ivacaftor (ELX/TEZ/IVA) for the treatment of cystic fibrosis as a case study to explore how alternative assumptions for (1) discounting, (2) utility measures, (3) disease management costs, and (4) static drug pricing impact cost-effectiveness outcomes. Materials and methods: Cost-effectiveness of ELX/TEZ/IVA was evaluated using base-case inputs and assumptions reflecting standard CEA methods and was then compared with cost-effectiveness estimates obtained with alternate assumptions: (1) applying a lower discount rate to health benefits (1.5%) than costs (3%); (2) including a treatment-specific utility increment; (3) excluding disease management costs incurred during the period of extended survival attributable to ELX/TEZ/IVA treatment; and (4) decreasing the price of ELX/TEZ/IVA following loss of exclusivity. Results: Modifying assumptions for these four factors together reduced the ICER by 75% from the base case, with the largest reduction (45%) occurring when the price trajectory was modified to allow for generic entry. Differential discounting, use of a treatment-specific utility increment, and exclusion of additional disease management costs each individually reduced the ICER by 36%, 14%, and 10%, respectively, from the base case. Conclusions: This study illustrates the impact that modifications to standard CEA methods may have on measures of cost-effectiveness for rare, chronic diseases.